2018
DOI: 10.3390/md16090340
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds from Marine Organisms: Potential for Bone Growth and Healing

Abstract: Marine organisms represent a highly diverse reserve of bioactives which could aid in the treatment of a wide range of diseases, including various musculoskeletal conditions. Osteoporosis in particular would benefit from a novel and effective marine-based treatment, due to its large disease burden and the inefficiencies of current treatment options. Osteogenic bioactives have been isolated from many marine organisms, including nacre powder derived from molluscan shells and fucoidan—the sulphated polysaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 103 publications
0
46
0
Order By: Relevance
“…Beside the important and predominant composition in agar, Gracilaria spp. constituents include carbohydrates, proteins, lipids, minerals and several other bioactive compounds [17,18]. These latter include, but are not limited to, polyphenols, alkaloids, polyketides, cyclic peptides, phlorotannins, sterols, diterpenoids, quinones and glycerols [19].…”
Section: Introductionmentioning
confidence: 99%
“…Beside the important and predominant composition in agar, Gracilaria spp. constituents include carbohydrates, proteins, lipids, minerals and several other bioactive compounds [17,18]. These latter include, but are not limited to, polyphenols, alkaloids, polyketides, cyclic peptides, phlorotannins, sterols, diterpenoids, quinones and glycerols [19].…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidan suppressed Ca 2+ -dependent endocytosis, potentially by inhibition of agonist-induced Ca 2+ responses [23]. Whilst the present study identified endochondral ossification, fucoidan has been associated with bone cell differentiation [24], but not specifically with endochondral ossification, an interaction that remains to be verified.…”
Section: Discussionmentioning
confidence: 47%
“…Marine coral is a natural bioceramic which has been examined as a graft for bone repair due its inherent porosity and high compressive stiffness [4][5][6][7][8][9]. However, the field of bone tissue engineering is increasingly moving away from the fabrication of such 'hard' scaffolds.…”
Section: Introductionmentioning
confidence: 99%